2015
DOI: 10.1093/mnras/stv1296
|View full text |Cite
|
Sign up to set email alerts
|

Improving pulsar timing precision with single pulses

Abstract: The measurement error of pulse times of arrival (TOAs) in the high S/N limit is dominated by the quasi-random variation of a pulsar's emission profile from rotation to rotation. Like measurement noise, this noise is only reduced as the square root of observing time, posing a major challenge to future pulsar timing campaigns with large aperture telescopes, e.g. the Five-hundred-metre Aperture Spherical Telescope and the Square Kilometre Array.We propose a new method of pulsar timing that attempts to approximate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, searches for multiple sinusoids are computationally prohibitive, and we have visually examined the timing residuals for all 151 pulsars to search for any additional "obvious" modulation, finding none. As noted by Kerr (2015), the presence of strong timing noise causes sensitivity to coherent sinusoids to scale roughly as the square root of observing span. Thus, for most of our sample, substantial further observations will be required to detect modulations with lower amplitude.…”
Section: Search For Periodic Signalsmentioning
confidence: 96%
“…However, searches for multiple sinusoids are computationally prohibitive, and we have visually examined the timing residuals for all 151 pulsars to search for any additional "obvious" modulation, finding none. As noted by Kerr (2015), the presence of strong timing noise causes sensitivity to coherent sinusoids to scale roughly as the square root of observing span. Thus, for most of our sample, substantial further observations will be required to detect modulations with lower amplitude.…”
Section: Search For Periodic Signalsmentioning
confidence: 96%
“…Besides gravitational wave, the spin-orbit coupling effect can be observed in pulsar timing observation. The correction to orbital precession would introduce extra shift of pulses received by a distant observer, and the spin precession and nutation could lead to the variation of pulse profiles, the detection of which has been shown to be possible (Kerr 2015). To estimate the effect of spin's precession and nutation, we adopt a toy model, using the light house model of pulsar here, as shown in Fig.…”
Section: Observational Prospectsmentioning
confidence: 99%
“…For the purpose of this analysis, the shoulders, which are not perfectly resolved but seen reproducibly, are regarded as band-heads or subheads. We note that a very weak shoulder appears on the blue edge of the spectrum of Kerr et al (1996) and on two or three of the lines-of-sight in Galazutdinov et al (2002).…”
Section: Figmentioning
confidence: 76%
“…It has been demonstrated that the carrier of many of the DIBs are most probably free flying molecules (ions or radicals) (Ehrenfreund and Foing 1996;Sarre et al 1995;Kerr et al 1988; Motylewski et al 2000). Several attempts at spectroscopic analysis including rotational contour modeling have made plausible fits of the λ6614 DIB (Kerr et al 1996;Schulz et al 2000;Cami et al 2004;Oka et al 2013;Bernstein et al 2015;Marshall et al 2015) and the DIB near 5797Å (Edwards and Leach 1993;Rouan et al 1997;Huang and Oka 2015). Dahlstrom et al (2013) report that these two highly correlated DIBs show similar anomalous broadening in the spectrum of Herschel 36.…”
mentioning
confidence: 99%